Practical stylistics : - Widdowson, H. G. (Oxford University Press, 1992)
This book takes a particular perspective on the nature of poetry and follows this through to proposals for teaching. It focuses attention on how the use of language in short poems can set up conditions for individual interpretation and the representation of reality in ways other than those which are established by normal social convention. This view of poetry, it is argued, leads to a recognition of its essential role in education, and provides a set of principles for an approach to teaching it which integrates the study of language and literature.